Respuesta :
Answer:I'm not sure but i think it's y=3/-2x+3
Step-by-step explanation:First you solve for m using y2-y1 over x2-x1. Then you plug in whichever point to solve for b.
Answer:
3x + 2y = 6
Step-by-step explanation:
y = mx + c where m is the slope of p and c is the y-intercept of p
m = [tex]\frac{y_{2}-y_{1} }{x_{2}-x_{1}}=\frac{-3-6}{4--2}=\frac{-9}{6}=\frac{-3}{2}[/tex]
y = -3/2 x + c
To get c use one of the two points to substitute the x and y in the equation
[tex]6=\frac{-3}{2}(-2)+c[/tex]
6 = 3 + c
6 - 3 = c
y = -3/2x + 3 Multiply both sides by 2
2y = -3x + 6
2y + 3x = 6
3x + 2y = 6